2002
DOI: 10.2307/3078959
|View full text |Cite
|
Sign up to set email alerts
|

An Mhc Component to Kin Recognition and Mate Choice in Birds: Predictions, Progress, and Prospects

Abstract: The major histocompatibility complex (Mhc) has been identified as a locus influencing disease resistance, mate choice, and kin recognition in mammals and fish. However, it is unclear whether the mechanisms by which Mhc genes influence behavior in mammals are applicable to other nonmammalian vertebrates such as birds. We review the biology of Mhc genes with particular reference to their relevance to avian mating and social systems. New genomics approaches recently have been applied to the Mhcs of chickens, quai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 57 publications
2
68
0
Order By: Relevance
“…Together, these results have led us to wonder whether odors may also play a role in mate choice (Zelano and Edwards, 2002). The potential that scent-based cues contribute to mate choice decisions has been typically overlooked in birds [for exceptions, see Douglas (Douglas, 2008); Hagelin (Hagelin, 2004) and Hagelin and Jones (Hagelin and Jones, 2007)] but kin recognition is mediated by scent in a wide range of vertebrates, including humans (Wedekind et al, 1995), mice (Yamazaki et al, 1976;Yamazaki et al, 1979), fish (Reusch et al, 2001) and lizards (Olsson et al, 2003).…”
Section: Future Directionsmentioning
confidence: 99%
“…Together, these results have led us to wonder whether odors may also play a role in mate choice (Zelano and Edwards, 2002). The potential that scent-based cues contribute to mate choice decisions has been typically overlooked in birds [for exceptions, see Douglas (Douglas, 2008); Hagelin (Hagelin, 2004) and Hagelin and Jones (Hagelin and Jones, 2007)] but kin recognition is mediated by scent in a wide range of vertebrates, including humans (Wedekind et al, 1995), mice (Yamazaki et al, 1976;Yamazaki et al, 1979), fish (Reusch et al, 2001) and lizards (Olsson et al, 2003).…”
Section: Future Directionsmentioning
confidence: 99%
“…These olfactory receptor genes, related to two orthologs in human (OR5U1 and OR5BF1 ), appear to have expanded within birds relatively recently to constitute the majority of the over 200 olfactory receptor genes in the chicken genome. The expansions of these genes could conceivably be part of the genetic mechanism linking the immune and olfactory systems with mate choice, kin recognition, and social interactions in birds (Zelano and Edwards, 2002). Other gene expansions were probably also important for key innovations in birds, such as expansions in the keratin gene family, which are the proteinaceous building blocks of feathers and therefore vital for thermoregulation, sexual display, and flight.…”
mentioning
confidence: 99%
“…It has been suggested that MHC-dependent mating preferences in mice 'could not be much more than a quirk of nature without general significance' (Klein et al, 1993). However, several recent studies have found evidence for MHC-dependent mating preferences in other taxa, including fish, reptiles, and even birds (Zelano and Edwards, 2002;Bernatchez and Landry, 2003;Milinski, 2006;Havlicek and Roberts, 2009). The most interesting implication of these studies is that they provide a potential example of how mating preferences can generate selection and evolution of genes that control immune recognition of pathogens and parasites.…”
Section: Sexual Selectionmentioning
confidence: 99%